MAFIC AND ULTRAMAFIC XENOLITHS IN SAN BARTOLO LAVA FIELD: NEW INSIGHTS ON THE ASCENT AND STORAGE OF STROMBOLI MAGMAS - Laiolo M.; Cigolini C. (My University, 2006)
Mafic and ultramafic xenoliths are well represented within a large basaltic lava field of Stromboli. These basalts, known as San Bartolo lavas, show a high-K calc-alkaline (HKCA) affinity and were erupted <5 ka BP. Xenoliths consist of olivin-gabbro, gabbronorite, anorthosite, dunite, wehrlite and clinopyroxenite. Thermobarometric estimates for the crystallization of gabbroic materials show minima equilibration pressures of 0.17-0.24 GPa, at temperatures ranging from 940 to 1,030°C. These materials interacted with hydrous ascending HKCA basaltic magmas (with temperatures of 1,050-1,100°C) at pressures of about 0.2-0.4 GPa. These pressure regimes are nearly identical to those found for the crystallization of phenocrystic phases within HKCA basaltic lavas. Gabbroic inclusions are regarded as cumulates and represent crystallized portions of earlier HKCA Strombolian basalts. Dunite and wehrlite show porphyroclastic-heterogranular textures, whereas the clinopyroxenite exhibit a mosaic-equigranular texture typical of mantle peridotites. These ultramafic materials are in equilibrium with more primitive basaltic magmas (under moderately hydrous and anhydrous conditions) at pressures of 0.8-1.2 GPa, which is below the crust-mantle transition, located at about 20 km depth under Stromboli. Major and trace element distributions indicate comagmatism between the host basaltic lava and the mafic and ultramafic inclusions. REE patterns for mafic nodules are relatively regular and overlap the field of basaltic lavas (HKCA). They show moderate to high LREE enrichments and moderate enrichments in HREE relative to chonrites. Spider diagrams also show significant similarities between the lavas and the mafic-ultramafic xenoliths as well. During their ascent, primitive Strombolian magmas may be stored in upper-mantle regions where they interact with peridotitic materials and partly differentiate (to give dunite and wehrlite) before migrating to upper crustal levels. In this region, hydrous basaltic magmas (with estimated water contents of 2-3.5 wt%) are stored in the subvolcanic environment, and are allowed to crystallize the gabbroic materials before reaching the surface under nearly anhydrous conditions. © Springer-Verlag 2005.
Keywords: BASALTIC MAGMA; ROCK-MELT INTERACTIONS; THERMOBAROMETRY; XENOLITHS